U.S. economic involvement. (1987., 1987)
The Reagan Doctrine finds little support among the American people. A traditional lack of enthusiasm f economic aid, a positive dislike for military aid, and a substantial concern that the latter will only get us military involved in Central America add up to a limited support for the President's policy. Further, the notion of "interdependence" between our domestic economy and our economy policy took something of a beating in the period 1982-86 as the American people gave diminished priority to economic issues in general.
Photocopy.
John E Reilly (ed.) American Public Opinion and U.S. Foreign Policy 1987. The Chicago Council on Foreign Relations.
Keywords: United States -- Economic conditions